The Impact of Anesthetic State on Spike-Sorting Success in the Cortex: A Comparison of Ketamine and Urethane Anesthesia - Hildebrandt, K. Jannis; Sahani, Maneesh; Linden, Jennifer F. (Frontiers in Neural Circuits, 2017)
Spike-sorting is an essential first step in most analyses of extracellular in vivo electrophysiological recordings. Here we show that spike-sorting success depends critically on characteristics of coordinated population activity that can differ between anaesthetic states. In tetrode recordings from mouse auditory cortex, spike-sorting was significantly less successful under ketamine/medetomidine (ket/med) than urethane anaesthesia. Surprisingly, this difficulty with sorting under ket/med anaesthesia did not appear to result from either greater millisecond-scale burstiness of neural activity or increased coordination of activity among neighbouring neurons. Rather, the key factor affecting sorting success appeared to be the amount of coordinated population activity at long time intervals and across large cortical distances. We propose that spike-sorting success is directly dependent on overall coordination of activity, and is most disrupted by large-scale fluctuations in cortical population activity. Reliability of single-unit recording may therefore differ not only between urethane-anaesthetized and ket/med-anaesthetized states as demonstrated here, but also between synchronized and desynchronized states, asleep and awake states, or inattentive and attentive states in unanaesthetized animals.